Analysis of the Effect of Quality Price and Brand Image on Used Clothing Purchasing Decisions in Pringgarata Village, Central Lombok Regency - Asri Julianti; Hailuddun; Masrun, Masrun (Tinta Emas Institute, 2023)
This research addresses the phenomenon of imported secondhand clothing sales in Pringgarata Village, Central Lombok Regency, Indonesia, which has been present for a considerable duration. This phenomenon emerged as an alternative during the economic crisis in 1997 and due to the limitations of domestically produced clothing. The research aims to analyze the impact of price, quality, and brand image on the purchase decisions of secondhand clothing in this area. The study employs a quantitative approach, involving consumers who purchase secondhand clothing as the population. A sample of 75 consumers is selected using the Slovin formula. Data analysis encompasses instrument testing, validity, reliability, classic assumptions, normality, multicollinearity, heteroskedasticity, hypothesis testing, and multiple linear regression analysis. The research findings indicate that price, quality, and brand image, both collectively and individually, have a positive and significant influence on purchase decisions. The independent variables collectively influence purchase decisions by 89.6%, while the remaining 10.4% is influenced by external factors beyond the scope of the study. These findings offer insights into the factors affecting secondhand clothing purchase decisions in Pringgarata Village and can be valuable in the context of the imported secondhand clothing business.